Dynamic Mechanism Design: A Myersonian Approach - Toikka, Juuso; Pavan, Alessandro; Segal, Ilya (Econometrica, 2014)
The copyright to this Article is held by the Econometric Society. It may be downloaded, printed and reproduced only for educational or research purposes, including use in course packs. No downloading or copying may be done for any commercial purpose without the explicit permission of the Econometric Society. For such commercial purposes contact the Office of the Econometric Society (contact information may be found at the website